Love blooms in winter ebook - Copeland, Lori (The Dakota Diaries, 2012)
A romantic new book from bestselling author Lori Copeland that portrays God's miraculous provision even when none seems possible. 1892—Mae Wilkey's sweet next-door neighbor, Pauline, is suffering from old age and dementia and desperately needs family to come help her. But Pauline can't recall having kin remaining. Mae searches through her desk and finds a name—Tom Curtis, who may just be the answer to their prayers. Tom can't remember an old aunt named Pauline, but if she thinks he's a long-lost nephew, he very well may be. After two desperate letters from Mae, he decides to pay a visit. An engagement, a runaway train, and a town of quirky, loveable people make for more of an adventure than Tom is expecting. But it is amazing what can bloom in winter when God is in charge of things.